Pengaruh Bimbingan Kelompok dengan Teknik Role Playing dalam Meningkatkan Pemahaman Pelecehan Seksual - Ervira Damayanti; Rochani Rochani; Arga Satrio Prabowo (Guidance : Jurnal Bimbingan dan Konseling, 2023)
This study aims to determine the effect of group guidance using role playing techniques in increasing knowledge of sexual harassment in grade VII students at SMPN 1 Cikeusik. This study used a quasi-experimental design method. The population of this study was 68 grade VII students at SMPN 1 Cikeusik, with a total sample of 10 students with 6 students as the control group and 4 students as the experimental group which were taken through purposive sampling technique. The research instrument used was a multiple choice questionnaire with a Guttman scale. Based on the Mann-Whitney U test showing the Asymp.Sig.(2-tailed) value of 0.010 <0.05, it can be concluded that "Hypothesis Accepted (Ha)". Thus it can be said that there are differences in results between the experimental group that was given treatment and the control group that was not given treatment. Because there is a significant difference, it can be said that there is an effect of group counseling with role playing techniques in increasing the knowledge of sexual harassment in class VII students.